(3bUI GdMLGL heG LQi dg eY eMeO Hf Rjf GdYGHOjfs - (3QhGjI(B: (3CHh YHO Gddg GdcQNjs ((3eMeO GdegOhjs)
(3ChdgG (B:s
(3GdMeO ddg QH GdYGdejf bGd CHh YHO Gddg GdcQNj MVQJ PGJ jhe eLdS GdMLGL Hf jhSa GdKbaj hGdfGS Mhdgs
(3BNQgG (B:s
(3agPg dG JLhR Ydjg GdddYfI dYdeg hGdQMeI dXdeg agh ehbha hgPG eG GfJgi EdjfG ef bUI GdMLGLs
(3eUOQ GbJfGA GdCUd (B:s
(3OGQ GdcJH GdbWQjIs
(3ehGUaGJ GdhYGA (B:s
(3Qbej edhfs
(3ehGUaGJ GdfSNI (B: s
(3ceGd GdfSNI (B:s
Keywords: (3GdJGQjNs